Effect of dipping number on the fabricated silica ceramic membranes via sol dip-coating method - Kahlib, Nor Amyra Zulianey; Mohd Daud, Farah Diana; Mel, Maizirwan; Ahmad Azhar, Ahmad Zahirani; Hassan, Noor Azlina (Penerbit Akademia Baru, 2017)
Received 22 December 2016 Received in revised form 28 January 2017 Accepted 4 April 2017 Available online 21 April 2017 Membrane technologies have received high interest in the separation gas mixture. The ceramic inorganic membranes have possessed high permeability, excellent thermal, chemical and mechanical stabilities compared to conventional polymer membranes. This work presents the fabrication of silica ceramic membrane by sol dip-coating method. The tubular support was dipped into the solution of tetrethylorthosilicate (TEOS), distilled water and ethanol with the addition of nitric acid as a catalyst. The fabricated silica membrane was then characterized by (Field Emission Scanning Electron Microscope) FESEM and (Fourier transform infrared spectroscopy) FTIR to determine structural and chemical properties at different dipping number. FESEM images indicate that the silica has been deposited on the surface fabricated ceramic membrane and penetrate into the pore walls. However, number of dipping did not affect the intensity peak of FTIR analysis.